Abordări conceptuale și metodologii de măsurare a calității vieții. O analiză descriptivă - Buligescu, Bianca; Țoc, Sebastian (Calitatea Vieții, 2021)
The main objective of this paper is to describe the logic of the conceptual approaches regarding the quality of life, and to identify the main dimensions and measurable indicators of quality of life. The identification of the main conceptualizations of quality of life is an essential step, in the context in which quality of life is often ambiguous or has multiple meanings. Although often used as an umbrella term which encompasses many aspects of human life, we aim to describe the logic of the integrative approaches regarding well-being/ quality of life. The identification of the main dimensions and measurable indicators of quality of life with a brief description of those, will serve to operationalize a list of life quality dimensions.